Lipocalin 2 (LCN2) confers acquired resistance to almonertinib in NSCLC through LCN2-MMP-9 signaling pathway - Chen Shi; Cong Wang; Zhiwen Fu; Jinmei Liu; Yuanfeng Zhou; Bao Cheng; Cong Zhang; Shijun Li; Yu Zhang (Pharmacological Research, 2024)
Almonertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, is highly selective for EGFR-activating mutations as well as the EGFR T790M mutation in patients with advanced non-small cell lung cancer (NSCLC). However, the development of resistance inevitably occurs and poses a major obstacle to the clinical efficacy of almonertinib. Therefore, a clear understanding of the mechanism is of great significance to overcome drug resistance to almonertinib in the future. In this study, NCI-H1975 cell lines resistant to almonertinib (NCI-H1975 AR) were developed by concentration-increasing induction and were employed for clarification of underlying mechanisms of acquired resistance. Through RNA-seq analysis, the HIF-1 and TGF-β signaling pathways were significantly enriched by gene set enrichment analysis. Lipocalin-2 (LCN2), as the core node in these two signaling pathways, were found to be positively correlated to almonertinib-resistance in NSCLC cells. The function of LCN2 in the drug resistance of almonertinib was investigated through knockdown and overexpression assays in vitro and in vivo. Moreover, matrix metalloproteinases-9 (MMP-9) was further identiﬁed as a critical downstream eﬀector of LCN2 signaling, which is regulated via the LCN2-MMP-9 axis. Pharmacological inhibition of MMP-9 could overcome resistance to almonertinib, as evidenced in both in vitro and in vivo models. Our findings suggest that LCN2 was a crucial regulator for conferring almonertinib-resistance in NSCLC and demonstrate the potential utility of targeting the LCN2-MMP-9 axis for clinical treatment of almonertinib-resistant lung adenocarcinoma.